Expanding Walter J. Ong’s Relationist Spirit: A Bibliographic Review Article - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2023)
The pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955) is a tough act to follow. Question: Are there perhaps ways in which media ecology theorists today can follow his example by further developing themes in hismature work from the early 1950s onward? I have selected five themes from Ong’s 1982 book Orality and Literacy: The Technologizing of the Word in Methuen’s New Accents book series for attention in my bibliographic review. I have appropriated the word relationist for use here from Ong’s 1977 statement of what he himself styles as his relationist thesis about the historyof the word in Western cultural history. In brief, I suggest through my categorized and briefly annotated bibliography how media ecology theorists today can develop certain themes in Ong’s work by following what I am here styling as the relationist spirit that he himself followed in his mature work from the early 1950s onward.